RECONCEPTUALIZING TRIPLE BOTTOM LINE ACCOUNTING: A CRITICAL REVIEW OF STAKEHOLDER THEORY - Crescentiano Agung Wicaksono (CV. Fahr Publishing, 2025)
This study aims to reconceptualize the Triple Bottom Line (TBL) accounting framework by integrating it with stakeholder theory to address the long-standing limitations in sustainability measurement and reporting. Using a qualitative library research method, the study systematically reviews and synthesizes recent theoretical and empirical literature on TBL, stakeholder theory, and multi-capital accounting. The analysis reveals that while TBL has gained global traction, its application remains fragmented—particularly in measuring social and environmental performance—due to weak stakeholder integration and a lack of standardization in reporting frameworks. One of the key contributions of this study is the development of a theoretical model that aligns stakeholder salience with multi-capital measurement, offering a new approach to balance economic, social, and environmental priorities. The novelty of this research lies in proposing a stakeholder-responsive accounting framework that moves beyond symbolic disclosure practices and provides practical insights for advancing sustainability accounting in both developed and emerging economies. The findings emphasize the need for a shift from firm-centric to stakeholder-inclusive thinking, where organizations not only report but actively manage trade-offs between stakeholder interests. In conclusion, this study contributes to the theoretical refinement of TBL accounting by embedding stakeholder theory into its core logic, thus enhancing its relevance, accountability, and global applicability. The model offers a pathway for future empirical research and policy development that promotes sustainable and equitable business practices across sectors.